Capital Flows to EU New Member States : Does Sector Destination Matter? - Mitra, Pritha (Washington, D.C. : International Monetary Fund, 2011)
The recent boom-bust episode in Emerging Europe was largely the product of surges and sudden stops in capital inflows. This paper empirically argues that the sectors into which capital flows determines their impact on GDP growth. Applying data from EU New Member States, it is found that capital flows into real estate have a greater impact on swings in GDP than other sectors, irrespective of a country's exchange rate or fiscal policy. Consequently, as new waves of capital inflows spread to emerging markets, policies may usefully focus on supporting capital inflows towards economic sectors that minimize large swings in GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet